Real-Time Monitoring System for Forest Fire Prevention and Combat: A Case Study in the Brazilian Semi-Arid Region - Araújo, Tiago Brasileiro; Almeida, Damião Ribeiro de; Sobral, Igor Silva; Brasil, Hicaro Ferreira; Trevisan, Ester Pequeno; Sales, Anna Beatriz Gomes; Soares, Ana Lícia Ferreira; Lopes Filho, José Gomes (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Wildfires pose significant environmental, economic, and social challenges, particularly in dry tropical forest biomes, such as Caatinga in Brazil. Traditional firefighting approaches often lack real-time data, impacting the efficiency of firefighting teams. Problem: Current firefighting operations lack integrated technological tools that support decision-making with real-time data on fire outbreaks, weather, and regional geography. This gap in operational support can lead to delayed responses, increased resource consumption, and compromised safety. Proposed Solution: This study presents a comprehensive decision-support service that aggregates real-time data from IoT sensors, satellite imagery, and weather APIs into an integrated system. This service equips firefighting teams with advanced tools for tracking, weather updates, fire management, and strategic planning, centralizing actionable information to enhance response capabilities. IS Theory: The proposed system is based on General Systems Theory, which supports interconnected subsystems for data collection, analysis, and user interaction, collectively enhancing operational support and strategic planning in firefighting. Method: A case study approach was applied, implementing the service for a regional fire brigade. Data from various sources were collected, processed, and displayed through an integrated system, including both a mobile and web application. System performance was evaluated using quantitative and qualitative metrics. Results Summary: The decision-support service provides real-time fire monitoring and aids in efficient firefighting planning and operations. Positive feedback from users indicates improved situational awareness and resource allocation. Contributions and Impact in IS: This tool enhances Information Systems by enabling actionable insights and real-time operations. Its scalable architecture adapts to various biomes, showcasing the value of integrated technologies in managing complex challenges and transforming traditional disaster response practices.